Pesticide Toxicity Profile: Arsenical Herbicides - Frederick Fishel (EDIS)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of the arsenical herbicides registered for use in Florida.This document is PI-89, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November, 2005.